2021
DOI: 10.3390/molecules26206137
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Infrared Heating Conditions for Precooked Cowpea Production Using Response Surface Methodology

Abstract: The infrared heating of preconditioned cowpea improves its utilization and potential application in food systems. This study investigated the effect of optimizing preconditioning and infrared heating parameters of temperature and time on cooking characteristics of precooked cowpeas using response surface methodology (RSM). The moisture level (32–57%), infrared heating temperature (114–185 °C), and time of processing the seeds (2–18 min) were optimized using a randomized central composite design to achieve opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 35 publications
(61 reference statements)
0
8
0
Order By: Relevance
“…Several methods including soaking, precooking, and usage of alkaline salts treatments have been useful to decrease cooking time and enhancing the nutritional quality of pulses 5 7 . Recently, infrared heating, a novel thermal food processing technique has also been reported to significantly improved cooking characteristics of pulses such as cowpea 8 .…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Several methods including soaking, precooking, and usage of alkaline salts treatments have been useful to decrease cooking time and enhancing the nutritional quality of pulses 5 7 . Recently, infrared heating, a novel thermal food processing technique has also been reported to significantly improved cooking characteristics of pulses such as cowpea 8 .…”
Section: Introductionmentioning
confidence: 99%
“…It is an environmentally friendly thermal treatment and considered as an advanced thermal process that can be exploited in food processing. Different studies on infrared heating of cowpea grains have shown that the combination of varying moisture level, infrared radiation temperature and time could reduce its cooking time by more than 50%, improve sensory properties including appearance and color and protein quality of the infrared treated cowpea grains 3 , 8 , 11 , 12 . These processing conditions causes an increase in solubility of pectin responsible for rapid water uptakes, separation of cells along the cell wall and other physicochemical and structural changes of starch and protein as a result facilitated softening of cowpeas and reduction in the cooking time 8 , 11 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations